CONSUMER PERCEPTION OF ME TOO MARKETING IN BLUE PLATE SUSHI ADVERTISEMENT - Elena Ramadhani; Lintang Ratri Rahmiaji (Interaksi Online, 2026)
The development of advertisement has increased along with the uses of mobile phone, which have become an important channel for marketing communication. Brand awareness plays a significant role in shaping consumer trust and loyalty. Consumer with low brand recognition tend to show lower trust, while those with higher recognition demonstrate stronger loyalty and purchase intentions. Based on a pre-survey conducted in this study, Blue Plate Sushi demonstrates a combination of medium and high brand awareness. However, there’s a gap between the ideal concept of advertising and the reality of Blue Plate’s use of a Me Too marketing strategy. This study aims to explore consumer perceptions of the Me Too marketing approach applied by Blue Plate Sushi toward Philadelphia Sushi Bali. Using a qualitative method with a reception audience analysis based on Stuart Hall’s encoding decoding theory, data were collected through in-depth interviews. The findings reveal that most informants occupied a dominant position in perceiving Blue Plate’s advertisement as offering similar quality to Philadelphia Sushi Bali. Meanwhile, perceptions of Me Too marketing were largely negotiated, as informants acknowledged its effectiveness while simultaneously expressing concerns regarding originality and ethics. Overall, consumers were generally receptive to the advertisement, although Me Too marketing was not considered effective for building long-term brand originality and loyalty.